2022
DOI: 10.1126/sciadv.abn1832
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of photoprotection in dark-to-light transition—More than just a matter of excess light energy

Abstract: In nature, photosynthetic organisms are exposed to different light spectra and intensities depending on the time of day and atmospheric and environmental conditions. When photosynthetic cells absorb excess light, they induce nonphotochemical quenching to avoid photodamage and trigger expression of “photoprotective” genes. In this work, we used the green alga Chlamydomonas reinhardtii to assess the impact of light intensity, light quality, photosynthetic electron transport, and carbon di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 76 publications
6
45
0
Order By: Relevance
“…1) a marked increase (5 to 600-fold) in CCM transcript levels was observed in WT cells (Supplementary Fig. 3), in accordance with recent studies 28,32 ; this increase was strongly suppressed by CO2 and to a lesser extent by acetate, which did not affect CCM gene expression in the icl mutant (Supplementary Fig. 3).…”
Section: Cia5 Links Hl and Low Co2 Responsessupporting
confidence: 89%
See 4 more Smart Citations
“…1) a marked increase (5 to 600-fold) in CCM transcript levels was observed in WT cells (Supplementary Fig. 3), in accordance with recent studies 28,32 ; this increase was strongly suppressed by CO2 and to a lesser extent by acetate, which did not affect CCM gene expression in the icl mutant (Supplementary Fig. 3).…”
Section: Cia5 Links Hl and Low Co2 Responsessupporting
confidence: 89%
“…CO2 and CIA5 appear to be of paramount importance in signal integration and transduction, regulating expression of both photoprotection and CCM genes. For instance, CO2 represses the UV-B elicited, UVR8-mediated expression of LHCSR3, and CIA5 is absolutely required for this expression 28 . Moreover, our results have shown that high CO2 levels or the absence of CIA5 have a severe impact on LHCSR3 gene expression and, although HL can still induce LHCSR3 transcription, no protein is detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations